The Role of Lifestyle Medicine on Obesity Management in Primary Health Care: The Integration of Digitally Based Monitoring Systems - AlTaib, Hanan; Mutairi, Safiyah Al; Oliwi, Lina Al; Namlah, Lara AL; Eissa, Mohammed Al; Onizi, Fadyah Al; Shahrani, Amal AL; Anazi, Elham AL; Sofiani, Youssef Al; Mogeeth, Mohammed Abdul-; Konswa, Ayman Afifi; Kofi, Mostafa (Journal of Posthumanism, 2026)
Lifestyle medicine is an evidence‑based medicine that promotes comprehensive lifestyle modifications. The effective role of lifestyle medicine interventions in treating obesity is limited in Saudi Arabia. This study aims to measure the role of lifestyle medicine in obesity care through intelligent tools. Methods: This is a retrospective study with 419 patients in the LSM clinics of Wazarat Health Care Center in Family Medicine, Prince Sultan Military Medical City (PSMMC). The primary outcome is the change in weight parameters, including total body weight loss, waist circumference, and BMI. Results: A total of 419 patients were included in the current work. In 6 months of follow-up, a significant reduction in total body weight loss (TBWL) from 93.71±13.39 at baseline to 87.01±13.41 at 6 months. The absolute reduction was 6.70±7.85 % (p< 0.001), waist circumference (WC), and body mass index (BMI). Data were visualized through a dashboard monitoring system. Conclusion: The role of lifestyle interventions has shown clinically meaningful results in obesity management and weight parameters. The use of a dashboard monitoring system may improve the quality of services in obesity care